Pengaruh Permainan Tradisional Bola Bekel terhadap Keterampilan Sosial Anak di Taman Kanak-Kanak - Ambarwati, Menik; Agusniatih, Andi; Amrullah, Amrullah; Nirmala, Besse (Absorbent Mind, 2026)
Children’s social skills are essential for developing the ability to interact, cooperate, follow rules, and respect others. This study aimed to determine the effect of the traditional bola bekel game on the social skills of Group B children at TK Negeri Pembina Samporoa. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. Data were collected through observations conducted before and after the intervention and analyzed using descriptive percentages and a paired t-test. The results showed that the proportion of children categorized as Very Well Developed increased from 0% to 38.33%, while the Developed as Expected category increased from 25% to 40%. Conversely, the Beginning to Develop category decreased from 48.33% to 21.66%, and the Not Yet Developed category declined from 26.66% to 0%. The hypothesis test produced a calculated t-value of 16.185, which was higher than the t-table value of 1.782 (16.185 > 1.782). These findings indicate that the traditional bola bekel game had a significant positive effect on children’s social skills. Therefore, bola bekel can be used as a meaningful play activity to improve cooperation, interaction, rule-following, and respect among kindergarten children.